Strategi Pemasaran dan Pengolahan Limbah Kopi Gunung Gambar - Dharomesz, Vonezyo Yupanzara (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
This journal is made for the Community Service Work of Universitas Atma Jaya Yogyakarta’s students to assist the community to develop the potential of their village. This work is conducted in Kampung Village, Ngawen District, Gunung Kidul Regency, Special Region of Yogyakarta. In this study, a work program is performed by doing marketing strategies and processing of Gunung Gambar coffee waste. Several things to be considered are the village infrastructure, facilities, and village potentials that are owned and need to be developed. The result of this work is the opportunity which can be further developed by the local community so that it can be implemented by them. The village of Kampung has the potential of Mount Gambar's tourist attraction that hopefully with the tourism development strategy it is expected to be one of the new sources of livelihood in the village.